Rosai-Dorfman Disease: An Imposter of Plasma Cell Rich Diseases - Dehuri, Priyadarshini; Gochhait, Debasis; Basu, Debdatta; Siddaraju, Neelaiah (Annals of Pathology and Laboratory Medicine, 2018)
Rosai Dorfman Disease is a histiocytic disorder associated with painless cervical lymphadenopathy. The typical histomorhology includes dilated lymphatic sinuses with a lymphohistiocytic infiltrate with emperipolesis of lymphoid cells and plasma cells as the hallmark feature. We are highlighting a unique case of Rosai Dorfman disease presenting with generalized progressive lymphadenopathy in a 19 year old male, in whom diagnosis of RDD was established by fine needle aspiration cytology. The case that is discussed here is also worth documenting because of its unusual morphology which is dominated by plasma cells. We have also attempted to determine a possible association of this case of Rosai Dorfman disease with increased IgG4+ plasma cells and IgG4 related disease.